Correction: The first synthesis of N-acetylneuraminic acid 1, 7-lactone. Issue 22 (18th March 2015) - Colombo, Raffaele; Anastasia, Mario; Rota, Paola; Allevi, Pietro
<x xml:space="preserve">Abstract</x> Correction for 'The first synthesis of N-acetylneuraminic acid 1, 7-lactone' by Raffaele Colombo et al., Chem. Commun., 2008, 5517–5519.